2017
DOI: 10.1142/s0218127417300403
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Proportional Relationship Between Switching-Time Length and Fractal-Like Structure for Continuous Tracking Movement

Abstract: We investigate the relationship between the switching-time length T and the fractal-like feature that characterizes the behavior of dissipative dynamical systems excited by external temporal inputs for tracking movement. Seven healthy right-handed male participants were asked to continuously track light-emitting diodes that were located on the right and left sides in front of them. These movements were performed under two conditions: when the same input pattern was repeated (the periodic-input condition) and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In contrast, SHDS is a model of a non-autonomous system that explicitly incorporates temporal external inputs, allowing us to analyze the individual behaviors of the two systems. Although previous applications of SHDS to human movements have experimentally controlled external temporal inputs 17,18,25,26 , the present results were obtained during an actual match between two players without controlling for external inputs. Thus, incorporating this external temporal input into SHDS may enable us to elucidate the underlying principles of seemingly complex behaviors in human interactions.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, SHDS is a model of a non-autonomous system that explicitly incorporates temporal external inputs, allowing us to analyze the individual behaviors of the two systems. Although previous applications of SHDS to human movements have experimentally controlled external temporal inputs 17,18,25,26 , the present results were obtained during an actual match between two players without controlling for external inputs. Thus, incorporating this external temporal input into SHDS may enable us to elucidate the underlying principles of seemingly complex behaviors in human interactions.…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that the behavior of the system shows hysteresis and can be used to predict the next state. However, it has been confirmed that the regularities differ according to the length of time of the external input [55][56][57]. In this case, we focused on individual behavior during an interpersonal competitive situation; that is, we regarded the system as non-autonomous.…”
Section: Discrete Dynamical Systemmentioning
confidence: 99%
“…This suggests that behavior of the system shows hysteresis and can be used to predict the next state. However, it has been confirmed that the regularities differ according to the length of time of the external input [55][56][57]. In this case, we focused on individual behavior during an interpersonal competitive situation; that is, we regarded the system as non-autonomous.…”
Section: Switching Hybrid Dynamicsmentioning
confidence: 99%